2021
DOI: 10.1038/s41467-021-22761-5
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear receptor HNF4 drives a brush border gene program conserved across murine intestine, kidney, and embryonic yolk sac

Abstract: The brush border is comprised of microvilli surface protrusions on the apical surface of epithelia. This specialized structure greatly increases absorptive surface area and plays crucial roles in human health. However, transcriptional regulatory networks controlling brush border genes are not fully understood. Here, we identify that hepatocyte nuclear factor 4 (HNF4) transcription factor is a conserved and important regulator of brush border gene program in multiple organs, such as intestine, kidney and yolk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 80 publications
(88 reference statements)
1
31
0
Order By: Relevance
“…7d ). For example, the TF HNF4A is a crucial regulator for enterocyte cell identity 53 , 54 . Motif analysis revealed that different TF binding motifs showed different degree of enrichment among cell clusters, with the motif enrichment of HNF4A and HNF4G showing the largest variance (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7d ). For example, the TF HNF4A is a crucial regulator for enterocyte cell identity 53 , 54 . Motif analysis revealed that different TF binding motifs showed different degree of enrichment among cell clusters, with the motif enrichment of HNF4A and HNF4G showing the largest variance (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The finding here that Paneth cell gene expression is strongly enhanced by NCT demonstrates an important role for HNF4α in that cell type. While HNF4a had a strong effect on Paneth cells, that did not appear to be due to direct effects on Paneth cell genes, as a study of ChIP-seq in the intestine did not identify genes expressed in Paneth cells [ 11 ]. Rather, genes expressed in the brush border epithelium appeared to be directly downstream of HNF4a.…”
Section: Discussionmentioning
confidence: 99%
“…In the intestine, genetic deletion of HNF4α leads to loss of mucin-associated genes, increased intestinal permeability, loss of intestinal stem cell renewal (PMID: 31759926) and predisposes to inflammatory bowel disease [ 10 ] as well as loss of brush border genes [ 11 ]. In humans, HNF4α mRNA was decreased in intestinal biopsies from patients with inflammatory bowel disease (IBD) and HNF4α has been linked to IBD in multiple GWAS studies [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Small intestine crypt and villi were isolated from the proximal 10 cm of small intestine using methods we have previously reported ( 45 ). Colonic mucosal scrapings were collected from the entire colon.…”
Section: Methodsmentioning
confidence: 99%